Making Fiscal Space Happen : Managing Fiscal Policy in a World of Scaled-Up Aid - Debrun, Xavier (IMF Working Papers; Working Paper ;, 2006)
Debt relief and the scaling up of aid to low-income countries should allow for greater fiscal space for expenditure programs to create long-term growth and lower poverty rates. But designing a suitable medium-term fiscal framework that fosters a sustainable delivery of better public services and infrastructure while maintaining a credible commitment to fiscal prudence confronts many challenges. This paper discusses what low-income countries can do to shape fiscal policy frameworks that are ambitious in trying to absorb additional aid while still ensuring longer-term sustainability for government expenditure programs and finances. It suggests what approaches can be used to manage the greater fiscal policy risks associated with a scaled-up aid environment, including coordination with monetary policy. The paper also discusses what institutional changes are needed if donors and countries are to facilitate the implementation of a higher level of aid-financed spending programs.